THE EFFECT OF HALLYU (KOREAN WAVE) TOWARDS INTENTION TO VISIT TO SOUTH KOREA WITH DESTINATION IMAGE AS A MEDIATING VARIABLE - Juliana, Angel; Susilo, Clarissa Listya (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract.  This research was done in order to understand the effect of Hallyu (Korean Wave) towards intention to visit in tourist from Surabaya, with destination image as a mediating variable. This research is a quantitative research which uses questionnaire as a main tool to collect research data. This research uses SEM method to analyse the research data. Based on the data analysis, it was found that Hallyu (Korean Wave) has a positive and significant effect towards intention to visit, and destination image also has a positive and significant effect towards intention to visit. Based on the result, it is also found that destination image has a full mediating effect in the relationship between Hallyu (Korean Wave) and intention to visit. Abstrak.  Penelitian ini dilakukan untuk mengetahui pengaruh Hallyu (Korean Wave) terhadap niat berkunjung wisatawan asal Surabaya, dengan citra destinasi sebagai variabel mediasi. Penelitian ini merupakan penelitian kuantitatif yang menggunakan kuesioner sebagai alat utama untuk mengumpulkan data penelitian. Penelitian ini menggunakan metode SEM untuk menganalisis data penelitian. Berdasarkan analisis data ditemukan bahwa Hallyu (Korean Wave) berpengaruh positif dan signifikan terhadap niat berkunjung, dan citra destinasi juga berpengaruh positif dan signifikan terhadap niat berkunjung. Berdasarkan hasil penelitian, ditemukan pula bahwa citra destinasi memiliki efek mediasi penuh dalam hubungan antara Hallyu (Korean Wave) dan niat berkunjung.